Comparative Analytical Study of Madana Shalatu (Unripen Fruit of Randia Dumetorum Lam) and Phalapippali (Processed Fruits of Randia Dumetorum Lam) - A Study of Abhava Pratinidhi Dravya (International Journal of Ayurveda and Pharma Research, 2023)
Vamana is the Agrya karma for Kaphaja vikaras. Madanaphala - Randia dumetorum Lam is the drug of choice for Vamana karma because of its property – Anapayitwat (without untoward effect). Specific collection method, season and processing is required to get Phalapippali to possess above quality. Madana shalatu– Unripen fruits of Madanaphala is an Abhavapratinidhi dravya mentioned in Sushrutha Samhita and Ashtanga Hrudaya which does not require this processing- Samskara. So, in the present study comparative qualitative and quantitative physicochemical and phytochemical analysis of the Madana Shalatu, Pakwa Madanaphala  Ripen fruit of Madanaphala and Madanaphala Pippali– Processed fruits of Madanaphala has been carried out. Aim: 1. Pharmacognostic, Physicochemical and Phytochemical analysis of Madana Shalatu, Pakwa Madanaphala, Madanaphala Pippali. 2. Comparative qualitative and quantitative phytochemical analysis of Madana Shalatu, Pakwa Madanaphala, Madanaphala Pippali. Method: 1. Pharmacognostic study – Macroscopic study and Microscopic study. 2. Preliminary physico chemical analysis. 3. Qualitative phyto chemical evaluation of aqueous and alcoholic extracts of the test drugs. 4. Quantitative analysis– UV Spectrophotometry. Result: Microscopic study, qualitative phyto chemical evaluation of all test drugs did not showed much differences. In total saponin estimation by UV Spectrophotometry of methanol and Water extract of ripen processed fruits of Randia, Ripen fruits of Randia and Unripen fruits of Randia is found to contain 73.71, 83.23, 71.35 and 72.62, 92.44, 75.25µg DE/mL of Saponin content respectively. Conclusion: Quantity of Saponin which is the main active principle in Randia Dumetorum responsible for Vamana Karma was similar in the Madana Shalatu and in Phala Pippali, whereas it was highest in Pakwa Madanaphala, thus it may be used like Phala Pippali without any laborious process of Samskara. Further Toxicity studies and clinical trials are required to prove its safety and efficacy in humans.